2021
DOI: 10.3390/ijerph18094809
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter 10 (PM10) Is Associated with Epistaxis in Children and Adults

Abstract: The impact of atmospheric concentration of particulate matter ≤10 μm in diameter (PM10) continues to attract research attention. This study aimed to evaluate the effects of meteorological factors, including PM10 concentration, on epistaxis presentation in children and adults. We reviewed the data from 1557 days and 2273 cases of epistaxis between January 2015 and December 2019. Eligible patients were stratified by age into the children (age ≤17 years) and adult groups. The main outcome was the incidence and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
6
1
Order By: Relevance
“…While our data suggest possible racial factors that could predispose patients to variations in AVM rates between patient groups, it is important to emphasize the central role genetic inheritance plays in HHT. HHT displays genetic heterogeneity mostly caused by mutations in the ENG , ACVRL1 and SMAD4 genes 23. ENG mutations have been associated with pulmonary and brain AVMs, ACVRL1 mutations are associated with hepatic AVMs, and SMAD4 has been associated with juvenile-polyposis syndrome and gastrointestinal bleeding, which was consistent in our study 21 26.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While our data suggest possible racial factors that could predispose patients to variations in AVM rates between patient groups, it is important to emphasize the central role genetic inheritance plays in HHT. HHT displays genetic heterogeneity mostly caused by mutations in the ENG , ACVRL1 and SMAD4 genes 23. ENG mutations have been associated with pulmonary and brain AVMs, ACVRL1 mutations are associated with hepatic AVMs, and SMAD4 has been associated with juvenile-polyposis syndrome and gastrointestinal bleeding, which was consistent in our study 21 26.…”
Section: Discussionsupporting
confidence: 89%
“…With regards to a role between ambient pollution and epistaxis in patients with HHT, although one study demonstrated a positive relationship between epistaxis and PM10, our investigation did not find any association with epistaxis or any measure of air pollution through a multiple linear regression 23. However, our study did find significant differences in exposure to pollutants between racial groups, with particularly high AQI and PM10 exposures among those who identified as Hispanic or Latino.…”
Section: Discussioncontrasting
confidence: 85%
“…Multiple factors, such as infection, allergy, trauma, use of anticoagulants, and hypertension, have been evaluated as risk factors for epistaxis ( 3 , 4 ). It has been suggested that environmental factors, such as meteorological factors and air pollutants, are important factors that are closely associated with the occurrence of epistaxis and hospital visits due to epistaxis ( 5 , 6 ). Nunez et al demonstrated that the monthly rate of admissions for epistaxis was closely associated with the monthly ambient temperature ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological conditions and PM10 concentration were the exposure variables, and the data were obtained from Korea Meteorological Administration 75 ( https://web.kma.go.kr/eng/index.jsp ). Data on air pressure (hPa), wind speed (m/s), air temperature (°C), relative humidity (%), sunshine duration (h), amount of solar radiation (MJ/m 2 ), number of clouds (cloud cover) (1/10), and PM10 concentration (μg/m 3 ) are daily reported, and we collected these daily reported data from January 1, 2015, to August 31, 2019, were analyzed 8 .…”
Section: Methodsmentioning
confidence: 99%
“…Humidity has likewise been linked to pediatric epistaxis 7 . In addition to meteorological factors, air pollutants such as PM10 have also been recently shown to be associated with the incidence of epistaxis in children 4 , 8 .…”
Section: Introductionmentioning
confidence: 99%